The geometry and emplacement of conical sandstone intrusions - Cartwright, J; James, D; Huuse, M; Vetel, W; Hurst, A (2008)
Conical sandstone intrusions with a geometry comparable with that of many igneous sills have been identified using 3D seismic data from large areas of the North Sea and Faeroe-Shetland Basins. These intrusions are of reservoir scale, ranging from 100 to 2000 m or so in diameter, 50-300 m in height, and 1-80 m in thickness (aperture). They are concentrated in specific stratigraphic intervals in the Cenozoic fills of both basins. Two geometrical end members are recognised and defined here: 'apical cones' and 'flat-based bowls'. The former consist of inward dipping conical inclined sheets meeting at a prominent apex and the latter of similarly dipping discordant margins climbing from the edges of a concordant sheet. Both end members are associated with domal folds that are interpreted as resulting from the hydraulic elevation of the overburden during intrusion, and which are analogous to similar structures associated with bowl-shaped igneous sills. Measurements of aperture (ω) versus distance exhibit systematic relationships with the structural relief of these folds, offering a potentially predictive method for estimation of sandstone intrusion aperture and reservoir volume prior to drilling. A growth model for these end-member geometries is presented, drawing on existing theory for igneous sill emplacement. Aperture versus distance plots (ω -X) are used to illustrate two contrasting models for aperture inflation during propagation, but these require much further data before any specific growth model can be adopted. © 2008 Elsevier Ltd. All rights reserved.